کێشەکانى وتنەوەى بابەتە کۆمەڵایەتییەکان لە ڕوانگەى مامۆستایانى پسپۆڕەوە - مصطفى, پ.د صابر بكر; محمود, باجەلان عمر (Sulaimani Journal for Humanities, 2023)
The research aims to: 1- Determining the type and level of impact of the problems facing the teachers of social studies from the point of view of the specialized teachers. 2- Determining the type and rate of problems in social subjects from the point of view of expert teachers according to the variables: A- Gender (male and female). b- Career years. To achieve these goals, the researcher used the descriptive research method, and the research community consisted of teachers specialized in social sciences in governmental and non-governmental primary schools in the city center of Sulaymaniyah for the academic year (2021-2022) and their number was (1778) teachers, and the study sample consisted of 384 teachers, and they were The research tool is in the form of a questionnaire, and the criteria for the problems were included in (95) paragraphs. The questionnaire consisted of (8) axes, after verifying the validity and stability of the scales, and this was applied to the research sample. The researcher used the appropriate statistical tools in this study, which are the arithmetic mean, the median, the standard deviation, the Pearson and Cronbach correlation and the T test. The results were obtained using the SPSS program. At the end of the study, the researcher reached the following conclusions: 1. Regarding the eight axes: the results were in favor of the economic and financial problems axis represented by the crises of the current situation in the Kurdistan Region) and were at the highest average level (2,772). 2- According to the gender variable, there are significant differences in the level of social issues problems among teachers who are at a high level in favor of the male gender. 3- According to the variable Career years, there are no significant differences in the level of problems of social issues among teachers. At the end of the study, some recommendations and suggestions were presented.